THE OCTOBER 1973 MIDDLE EAST WAR - Heitman, H.R (Scientia Militaria - South African Journal of Military Studies, 2012)
The events of the October 1973 Arab-Israeli war have led many to the conclusion that 'the tank' is dead or, at the very least, mortally wounded. This argument would appear to be based, at least in part, upon one basic and vital misconception: that 'the tank' and 'armour' are identical.